A close insight into the nature of intra- and intermolecular interactions in new Cu(II) Schiff base complexes derived from halogenated salicylaldehydes and allylamine: Theoretical and crystallographic studies. (15th November 2018) - Aryaeifar, Mahnaz; Amiri Rudbari, Hadi; Bruno, Giuseppe
Graphical abstract: Four halogenated Schiff base compounds were synthesized by reaction of halogenated salicylaldehydes (3, 5-dichlorosalicylaldehyde, 3, 5-dibromosalicylaldehyde, 3, 5-diiodosalicylaldehyde and 3-bromo-5-chlorosalicylaldehyde) with allyl amine in water as green solvent at ambient temperature. Their Cu(II) Schiff base complexes showed halogen-halogen, π–π, CH–π interactions and also metal–halogen secondary bonds in crystal packing. These interactions investigated by Hirshfeld surface analysis and theoretical calculations. Abstract: Although numerous Schiff base complexes have been synthesized and characterized, reports on Schiff base ligands and complexes derived from amines containing terminal allyl group are rare. In this work, four halogenated Schiff base compounds were synthesized by reaction of halogenated salicylaldehydes (3, 5-dichlorosalicylaldehyde, 3, 5-dibromosalicylaldehyde, 3, 5-diiodosalicylaldehyde and 3-bromo-5-chlorosalicylaldehyde) with allyl amine in water as green solvent at ambient temperature and characterized by elemental analyses, NMR ( 1 H and 13 C), and FT-IR spectroscopy. In continue, their Cu(II) complexes were synthesized and characterized by elemental analyses, FT-IR and single-crystal X-ray diffraction. All complexes show halogen-halogen, π–π, CH–π interactions and also metal–halogen secondary bonds in crystal packing. The coordination geometry around the Cu(II) in all reported compounds is best described as square planar with two axially elongated interactions named metal–halogen secondary bond (Cu…X), all beyond the sum of the corresponding vdW radii (3.421 Å for Cu…Cl in(Cl2 L)2 Cu, 3.463 Å for Cu…Br in(Br2 L)2 Cu, 3.486 Å for Cu…I in(I2 L)2 Cu and 3.467 Å for Cu…Cl in(BrClL)2 Cu ). The crystal structures have also been subjected to Hirshfeld surface analysis which reveals that approximately most of the close contacts correspond to relatively weak interactions. Also, all of the interactions in crystal packing have been analyzed by theoretical calculations.